Peningkatan Kemampuan Operasi Hitung Penjumlahan Melalui Animasi Powerpoint pada Murid Tunagrahita - Muhammad Al Isra Ramadhan; Wizerti Ariastuti Saleh (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research was motivated by the low ability of mentally retarded students in addition calculation operations. The aim of this research is to use PowerPoint animation media in learning to improve the mathematical abilities of students with intellectual disabilities. The type of research used is classroom action research (PTK) with a qualitative approach and carried out in two cycles. The subjects of this research were three mentally retarded students in class V SLB YPPLB Pangkep. Data collection includes tests, observations, and documentation as well as qualitative data analysis. The results of the study showed that the arithmetic addition ability of mentally retarded students in class V SLB YPPLB Pangkep school increased. So it can be concluded that using PowerPoint animation media can help improve the ability of mentally retarded students to calculate addition operations.